Manfaat Pengembangan Objek Wisata Pantai Air Manis terhadap Masyarakat - Annisa Azarin; Erwin Erwin; Lucky Zamzami (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to describe the implementation of the archipelago module course on social interaction in the independent student exchange activity program. This study used descriptive qualitative method. The subjects of this study were all students in the independent student exchange program at the University of Mataram. Collecting data using observation, interviews and documentation. The results of the study show that the implementation of the archipelago module has a positive impact on social interaction, namely increasing understanding and appreciation of Indonesia's cultural diversity. Improve communication skills, open job opportunities and increase self-confidence. Obstacles faced during implementation include; lack of qualified teaching staff, limited facilities and infrastructure, difficulties in accessing resources, differences in student backgrounds, lack of support and attention from the campus. The conclusion of this study is that the implementation of the Merdeka Student Exchange Program has a positive impact on social interaction between students, as well as increasing understanding and appreciation of Indonesia's cultural diversity. Meanwhile, in overcoming the obstacles encountered during the implementation of the Nusantara Module course, cooperation is needed between all parties involved in this program, be it the campus, teaching staff, or students. Keywords: Air Manis Beach, Community, Tourism Object Development,